The Application of AVR Codevision Software in Microprocessor and Microcontroller Programming Subjects at Muhammadiyah Vocational School Banda Aceh - Malahayati, Malahayati; Rais, Amien Refnas; Fachri, Muhammad Rizal; Akhyar, Akhyar (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
The rapid development of technology in the field of automation has emphasized the importance of understanding microprocessor and microcontroller programming among students. This research aims to investigate the influence of applying CodeVision AVR software on the learning outcomes of 11th-grade TAV students at SMK Muhammadiyah Banda Aceh. The CodeVision AVR software has the CodeWizard AVR feature, which makes it easier for beginners to create programs. This research uses the Classroom Action Research method with 3 cycles, and the research sample consists of 11th-grade TAV students. Data collection techniques include pre-tests, post-tests, group tests, and documentation. The research results show that the application of learning using CodeVision AVR software can improve students' learning outcomes. This can be seen from the average score obtained at the end of cycle III with an average score of 81.25. Meanwhile, in the group exam, the average score is 95.75. It can be concluded that there is an improvement in students' understanding and skills in the material taught through the AVR Application